VD_FINDINFO Jug / 2022 / 204 vom 2. September 2020 - VD Tribunal cantonal (2020)
ADMISSION PARTIELLE, FRAIS JUDICIAIRES | 123 ch. 2 al. 3 CP, 123 ch. 2 al. 4 CP, 181 CP, 19 al. 2 CP, 219 al. 1 CP, 48 CP, 98 CP, 426 al. 1 CPP (CH)